(untitled) (World Bulletin of Management and Law, 2023)
In this article, the real state of the labor market in the districts of Tashkent region is evaluated using the Frauchi index. Frauchi index is one of the indicators of the labor market, based on which regions of Tashkent region were divided into groups according to the state of the labor market and analyzed. Also, scientific proposals have been developed to improve the labor market situation and ensure employment of the population.